Analysing Factor Affecting Measles Immunization - Gita Sekar Prihanti; Tita Wisata; Rofwiun Rofwiun; Mariyah Giptiyah; Tira Anna Kasih; Nasrul Nasehati; Ulil Amri Pramadani; Mochamad Bilal (Saintika Medika, 2020)
Background: Immunization development program is one of the priority issues in national health that an effort to reduce the morbidity and mortality on children. East Java is one of province the number of incomplete children immunization that has reach 21% and children did not get immunization has reach 2.08 %. Objective: Knowing factors mother age, tradition, education, knowledge, income, work, attitude, siblings, family support, and health facilities has affect to the completeness of measles immunization in X public health center at Y city, Methods of the Research: This study used analytic observational with cross sectional design. Data analysis used Chi-Square test and logistic regression. The study involving 218 respondent consist of 114 mothers with children who have measles immunization and 104 mothers with children who do not immunize measles. Result and Discussion: There was a correlation between tradition (p = 0.020, OR = 4,428, CI = 95%), attitude (p = 0.00, OR = 5,616, CI = 95%), and maternal education (p = 0.000, OR = 0,236, CI = 95 %) on measles immunization with R value 0,234 in the amount of 23,4%. Conclusion:  There exist a need of health education and counseling for improving maternal education, tradition, and attitude. Support from family, public health center and community was necessary to increase completeness of children immunization especially measles vaccine